THE USE OF DISCOVERY LEARNING MODEL THROUGH VISUAL, AUDITORY, KINESTHETIC (VAK) APPROACH IN IMPROVING NATURAL SCIENCE LEARNING FOR THE FOURTH GRADE STUDENTS OF SD NEGERI 2 JATIROTO IN THE ACADEMIC YEAR 2014/2015 - Marlina, Marlina (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Use of Discovery Learning Model Through Visual, Auditory, Kinesthetic (VAK) Approach In Improving Natural Science Learning for the Fourth Grade Students of SD Negeri 2 Jatiroto In The Academic Year 2014/2015. The objectives of this research are to describe steps of using Discovery Learning model through Visual, Auditory, Kinesthetic (VAK) approach, to improve Natural Science learning about energy at the fourth grade, and to describe problems and solutions. This research is a collaborative Classroom Action Research (CAR). The research was conclude in three cycles consisting of planning, action, observation, and reflection in each cycle. The subjects were the fourth grade students of SD Negeri 2 Jatiroto totaling 21 students. The results of this research indicate that the use of Discovery Learning model through Visual, Auditory, Kinesthetic (VAK) approach conducted with appropriate steps can improve Natural Science learning at the fourth grade students of SD Negeri 2 Jatiroto in the academic year 2014/2015. Keyword: Discovery Learning, VAK, learning, Natural Science